2014
DOI: 10.1097/bpo.0b013e31829b2f61
|View full text |Cite
|
Sign up to set email alerts
|

Results of Cement versus Bone Graft Reconstruction after Intralesional Curettage of Bone Tumors in the Skeletally Immature Patient

Abstract: Level III: Retrospective comparison study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
0
20
1
Order By: Relevance
“…Ozaki et al reported lower recurrence with curettage and cementing compared to curettage and grafting alone, 17 and 37 %, respectively [44]. In a retrospective comparative study examining the effect of cement versus bone grafting in benign pediatric bone lesions, Wallace et al reported similar complication and recurrence rates, and Mankin et al also reported similar rates of recurrence when using bone graft or cement [19,43]. The application of PMMA to the predominantly pediatric population that is afflicted with ABC warrants consideration with regard to its long-term effects: PMMA is biologically inert without the potential for osseous incorporation, has no growth potential, can lead to stress shielding, thereby increasing the risk of future pathologic fracture, and as a foreign body, may act as a nidus for infection.…”
Section: Cementmentioning
confidence: 52%
See 1 more Smart Citation
“…Ozaki et al reported lower recurrence with curettage and cementing compared to curettage and grafting alone, 17 and 37 %, respectively [44]. In a retrospective comparative study examining the effect of cement versus bone grafting in benign pediatric bone lesions, Wallace et al reported similar complication and recurrence rates, and Mankin et al also reported similar rates of recurrence when using bone graft or cement [19,43]. The application of PMMA to the predominantly pediatric population that is afflicted with ABC warrants consideration with regard to its long-term effects: PMMA is biologically inert without the potential for osseous incorporation, has no growth potential, can lead to stress shielding, thereby increasing the risk of future pathologic fracture, and as a foreign body, may act as a nidus for infection.…”
Section: Cementmentioning
confidence: 52%
“…Similarly, polymethylmethacrylate (PMMA) cement in pediatric benign bone lesions can provide immediate stabilization for the resultant cavity, and it can act as a recurrence reducing adjuvant through its exothermic effect as the cement hardens [43]. With regard to reduction of recurrence, the evidence is mixed on the efficacy of cement.…”
Section: Cementmentioning
confidence: 99%
“…The effect of the cement on the physes in patients with an immature skeleton is controversial. 15 Wallace and Henshaw 16 argued that cementing had no negative effect, whereas Gasden et al has reported its undesirable outcomes. 17 The use of high-speed burring may be limited in patients with an immature skeleton as it may increase the damage to the physis or destruct the cartilage in the areas with subchondral bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy includes the use of liquid or aerosolised nitrogen that creates freezing temperatures that leads to a cytotoxic effect on the ABC lesion .Cryotherapy is done following curettage of the lesion .Cryotherapy though has a low recurrence rate ,is still not used widely as it has often led to complications like postoperative fracture ,skin necrosis and wound infection [1,4] . Polymethylmethacrylate (PMMA) cement is a biologically inert substance that helps in stabilisation of cavity in paediatric bone lesion and also as a recurrence reducing adjuvant through its exothermic reaction [5] . But PMMA also increases the risk of pathological fracture since it lacks the potential for osseous incorporation and has no growth potential.…”
Section: Discussionmentioning
confidence: 99%